2007
DOI: 10.1111/j.1365-2249.2007.03359.x
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 and NRAMP1/SLC11 A1 gene polymorphisms in Mexican mestizo patients with pulmonary tuberculosis

Abstract: SummaryTuberculosis remains one of the most important infectious diseases worldwide. Several studies have suggested that genetic factors may affect susceptibility to tuberculosis, but the specific genes involved have not yet been fully characterized. NRAMP1/SLC11 A1 and P2X7 genes have been linked to increased risk for tuberculosis in some African and Asiatic populations. To explore the potential role of these genes in the susceptibility to pulmonary tuberculosis in a Mexican mestizo population, we evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 47 publications
2
64
1
Order By: Relevance
“…Given the ability of various P2Y family receptors to regulate Ca 2+ and lipid signaling, it seems likely that P2X7 and various P2Y receptors act cooperatively to mediate the actions of extracellular ATP on killing of internalized mycobacteria or chlamydia. Such an interaction between P2X7R and another P2 receptor subtype(s) could explain the disparate associations of particular P2X7R polymorphisms with altered progression of tubercular phenotypes within different subgroups of human populations or mouse models [64,[68][69][70][71][72][73][74][75].…”
Section: P2x7r Regulation Of Phagosome Maturation and Microbial Killingmentioning
confidence: 99%
“…Given the ability of various P2Y family receptors to regulate Ca 2+ and lipid signaling, it seems likely that P2X7 and various P2Y receptors act cooperatively to mediate the actions of extracellular ATP on killing of internalized mycobacteria or chlamydia. Such an interaction between P2X7R and another P2 receptor subtype(s) could explain the disparate associations of particular P2X7R polymorphisms with altered progression of tubercular phenotypes within different subgroups of human populations or mouse models [64,[68][69][70][71][72][73][74][75].…”
Section: P2x7r Regulation Of Phagosome Maturation and Microbial Killingmentioning
confidence: 99%
“…Investigations evaluating the significance of P2X 7 polymorphisms and overall protein expression levels support the idea that cells need to correctly respond to extracellular ATP via P2X 7 for the mediation of several functions, including neurotransmission, mycobacterial killing, and appropriate cell death. Genetic analyses have linked P2X 7 polymorphisms to Mycobacterium tuberculosis (TB) infection and bipolar affective disorder [13,14,28,29]. The P2X 7 A1513C polymorphism, which results in mutation of Glu496 to Ala, has been associated with TB in two different population groups [13,14], and one report has shown that a SNP located in the promoter at position −762 is protective against the bacterium [28].…”
Section: P2x 7 Polymorphisms and Altered Expression Levels In Human Dmentioning
confidence: 99%
“…There are two P2 receptor subfamilies, the seven-transmembrane spanning P2Y G-protein-coupled receptors and the double membrane spanning P2X cation channels. There are at least eight P2Y family members (P2Y 1-2 , P2Y 4 , P2Y 6 , P2Y [11][12][13][14] ) and seven P2X receptors (P2X 1-7 ) [8,9]. All of the P2X receptors contain a short (<35 amino acids) intracellular N-terminal region, a large extracellular nucleotide-binding domain, and an intracellular C-terminus.…”
Section: General Properties Of P2xmentioning
confidence: 99%
See 2 more Smart Citations